2014
DOI: 10.1194/jlr.m042333
|View full text |Cite
|
Sign up to set email alerts
|

Obesity favors apolipoprotein E- and C-III-containing high density lipoprotein subfractions associated with risk of heart disease

Abstract: with an elevated risk of coronary heart disease (CHD) ( 1-5 ). However, evidence from randomized clinical trials that studied drugs that increased HDL-C has not been consistent with the hypothesis that HDL protects against CHD. In large-scale trials of novel cholesteryl ester transfer protein inhibitors, CHD incidence was not reduced despite substantial increases in HDL-C levels ( 6-8 ); trials of estrogen replacement therapy in postmenopausal women did not confi rm a protective effect on CHD despite increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 52 publications
4
34
0
1
Order By: Relevance
“…Two independent prospective studies showed that HDL cholesterol that contains or lacks apoC-III demonstrated opposite associations with the risk of coronary heart disease (CHD): HDL cholesterol that lacks apoC-III was inversely associated with CHD, whereas HDL cholesterol that contains apoC-III (small subfraction) was associated with a higher risk of CHD [16]. Further, the associations of apoE concentrations in HDL with cardiovascular risk significantly differ in the presence of apoC-III in that HDL with both apoE and apoC-III tended to be associated with a higher cardiometabolic risk [17,33,34]. Therefore, the heterogeneous lipoprotein subspecies deserve to be characterized in order to improve the disease risk prediction rather than relying on total lipid fractions [14].…”
Section: Discussionmentioning
confidence: 99%
“…Two independent prospective studies showed that HDL cholesterol that contains or lacks apoC-III demonstrated opposite associations with the risk of coronary heart disease (CHD): HDL cholesterol that lacks apoC-III was inversely associated with CHD, whereas HDL cholesterol that contains apoC-III (small subfraction) was associated with a higher risk of CHD [16]. Further, the associations of apoE concentrations in HDL with cardiovascular risk significantly differ in the presence of apoC-III in that HDL with both apoE and apoC-III tended to be associated with a higher cardiometabolic risk [17,33,34]. Therefore, the heterogeneous lipoprotein subspecies deserve to be characterized in order to improve the disease risk prediction rather than relying on total lipid fractions [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies show that apoC-III is an independent predictor of CVD risk and progression in humans (9,40,41), and that its presence on lipoproteins promotes their atherogenicity (8,(43)(44)(45). This is likely because apoC-III, expressed in both liver and the intestine, raises plasma TAG through the inhibition of hepatic clearance of TAG-rich chylomicrons and VLDLs, stimulates VLDL secretion, and modulates intestinal TAG trafficking (12,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that obese subjects have a higher prevalence of apoC-III-containing HDL particles compared with lean subjects, which have a higher prevalence of HDL particles without apoE or apoC-III [64]; apoC-III-containing HDL have been associated with CHD [65], suggesting that obese subjects have dysfunctional HDL particles with a lower protective ability, while normal-weight subjects have a higher prevalence of protective HDL particles.…”
Section: Role Of Apoc-iii In Trl Metabolismmentioning
confidence: 98%